Tannin-based flax fibre reinforced composites for structural applications in vehicles - Zhu, Jinchun; Abhyankar, Hrushikesh; Nassiopoulos, Elias; Njuguna, James A. K. (Cranfield University, 2012)
Innovation is often driven by changes in government policies regulating the industries, especially true in case of the automotive. Except weight savings, the strict EU regulation of 95% recyclable material-made vehicles drives the manufactures and scientists to seek new 'green materials' for structural applications. With handing at two major drawbacks (production cost and safety), ECHOSHELL is supported by EU to develop and optimise structural solutions for superlight electric vehicles by using bio-composites made of high-performance natural fibres and resins, providing enhanced strength and bio-degradability characteristics. Flax reinforced tannin-based composite is selected as one of the candidates and were firstly investigated with different fabric lay-up angles (non-woven flax mat, UD, [0, 90°]4 and [0, +45°, 90°, −45°]2) through authors' work. Some of the obtained results, such as tensile properties and SEM micrographs were shown in this conference paper. The UD flax reinforced composite exhibits the best tensile performance, with tensile strength and modulus of 150 MPa and 9.6 MPa, respectively. It was observed that during tension the oriented-fabric composites showed some delamination process, which are expected to be eliminated through surface treatment (alkali treatment etc.) and nanotechnology, such as the use of nano-fibrils. Failure mechanism of the tested samples were identified through SEM results, indicating that the combination of fibre pull-out, fibre breakage and brittle resins failure mainly contribute to the fracture failure of composites.